How "Schools of Choice" Can Improve the Public School System - Harley, Kevin; Commonwealth Foundation for Public Policy Alternatives, Harrisburg, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Public "schools of choice" refers to a new trend in educational policy that involves various forms of competition and choice. The initiatives of individual states range from authorizing magnet schools to allowing parents to send children to neighboring school districts. What these programs have in common is that parents, as consumers of education, are given a choice in where to send their children. The state that has had the most success with public schools of choice is Minnesota, but Massachusetts has also experimented successfully with choice programs for about 20 years. In Pennsylvania, the school of choice option that has been used most often is that of magnet schools. Positive results have been achieved in some Pennsylvania cities, but should not be seen as the only answer to public school problems. Other states have implemented a variety of approaches, and their programs illustrate that the cost of funding public schools of choice depends on the size and scope of the program. Negative aspects of schools of choice that critics have examined are impacts on racial integration, the difficulty of administering programs and districts, and the impact on teachers. However, these issues can be addressed. Control of education should be given back to those who are closest to the schools, students, parents, and local school boards. (SLD)
Availability: The Commonwealth Foundation, 600 North Second Street, Suite 400, Harrisburg, PA 17101 ($3).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Change; Educational Policy; Elementary Secondary Education; Free Choice Transfer Programs; Magnet Schools; Parent Participation; Public Schools; Racial Composition; School Choice; School Desegregation; School Restructuring; State Programs; Urban Schools; Pennsylvania; Massachusetts -- Minnesota; Opinion Papers; Reports, Evaluative